2018
DOI: 10.3340/jkns.2017.0404.012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Aneurysms in Judicial Precedents

Abstract: ObjectiveFrom November 30, 2016, the Korean Government carried the revised Medical Dispute Mediation and Arbitration Act into effect. Mediation will start automatically without agreements of the defendant, when the outcome of the patient was death, coma more than a month or severe disability. Cerebral aneurysm has a definite risk of bad outcome, especially in the worst condition. Any surgical intervention to this lesion has its own high risk of complications. Recently, Seoul central district court decided 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Medicolegal implications which are faced by the endovascular specialists due to procedural complications have been a great concern in some of the recent publications. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Medicolegal implications which are faced by the endovascular specialists due to procedural complications have been a great concern in some of the recent publications. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Due to procedural complications, some endovascular specialists have to face medico-legal implications. [32] The major disadvantage of endovascular procedures with stent-assisted coiling for basilar top aneurysm and trunk aneurysm is the risk of compromising blood flow to brain stem perforators. A study conducted by Richling et al showed that there is a 92% occlusion rate in basilar bifurcation aneurysm size <10 mm, but in aneurysm size of 10 mm or above, the occlusion rate is 61%.…”
Section: After the Invention Of Detachable Platinum Coils To Treat An...mentioning
confidence: 99%
“…Cerebral aneurysm formation is caused by various factors, including genetic factors such as fibromuscular dysplasia, autosomal dominant polycystic kidney disease, tuberous sclerosis, and arteriovenous malformations (AVM), as well as environmental factors such as smoking and alcohol abuse, and other influence such as atherosclerosis, hypertension, or advanced age [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by epidemiologists have revealed the rate of incidental aneurysms to be 7% (95% confidence interval [CI]) [5][6][7][8][9], with a corresponding occurrence of clinoid segment aneurysms at 3% (95% CI) [2][3][4]. Globally it is estimated to be roughly 3.2%, at an average age of 50 years, and with the overall gender ratio of 1: 1.…”
Section: Introductionmentioning
confidence: 99%